Customer engagement in tourism and hospitality research - Loureiro, S. M. C.; Raouf, A. R.; Ramkissoon, H.; Hollebeek, L. (Handbook of customer engagement in tourism marketing, 2023)
Customer engagement (CE), defined as a customer's resource investment in his/her brand or firm interactions, has evolved into an important tourism and hospitality marketing metric in the last decade. However, despite existing insight in this area, dynamic CE remains in flux, requiring further investigation. In this chapter, we discuss CE's key theoretical foundation/underpinnings, perspectives, operationalization(s)/measurement, antecedents, consequences, mediators, moderators, approaches and methods, thus offering a foundation upon which the remainder of this book is built.